2021
DOI: 10.1002/lno.11973
|View full text |Cite
|
Sign up to set email alerts
|

As above, so below? Effects of fungicides on microbial organic matter decomposition are stronger in the hyporheic than in the benthic zone

Abstract: Microbial organic matter decomposition is a critical ecosystem function, which can be negatively affected by chemicals. Although the majority of organic matter is stored in sediments, the impact of chemicals has exclusively been studied in benthic systems. To address this knowledge gap, we assessed the impact of a fungicide mixture at three concentrations on the decomposition of black alder leaves in the benthic and hyporheic zone. We targeted two sediment treatments characterized by fine and coarse grain size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 121 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…For instance, organic matter decomposition experiments are often conducted in aerobic habitats (i.e., water column or benthic surface) rather than in anaerobic habitats (i.e., hyporheic zone) where organic matter may also accumulate. For instance, Bollinger et al (2022) observed a 2‐fold higher fungicide effect in the hyporheic zone on microbial leaf litter decomposition compared with the benthic zone. Garcia‐Cruz et al (2010) agreed on the presence of chlorophenols (i.e., 2,4‐D) in environments where sulfate‐reducing bacteria are present and cause toxicity and inhibition on sulfate respiration.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, organic matter decomposition experiments are often conducted in aerobic habitats (i.e., water column or benthic surface) rather than in anaerobic habitats (i.e., hyporheic zone) where organic matter may also accumulate. For instance, Bollinger et al (2022) observed a 2‐fold higher fungicide effect in the hyporheic zone on microbial leaf litter decomposition compared with the benthic zone. Garcia‐Cruz et al (2010) agreed on the presence of chlorophenols (i.e., 2,4‐D) in environments where sulfate‐reducing bacteria are present and cause toxicity and inhibition on sulfate respiration.…”
Section: Resultsmentioning
confidence: 99%